Local Wisdom in Animal Conservation and Animal Use as Medicine of Orang Rimba in Bukit Duabelas National Park, Jambi - Burhanuddin Masyud; Nela Resta Felayati; Tutut Sunarminto (Jurnal Manajemen Hutan Tropika, 2020)
Orang Rimba is an ethnic group consisting of several indigenous groups that live in harmony with nature. This study aims to analyze the local wisdom in animal conservation and differences in the use of animals as medicines of Orang Rimba groups (Makekal, Air Hitam, and Terap groups). Data were collected through field observation and in-depth interviews with key persons. The results showed that local wisdom in animal conservation was indicated by the regulation in the use of animals through the stipulation that certain animals considered as gods must not be hunted, and that customary spaces use is prohibited. There were 68 animal species used for various needs, 20 species (29.41%) were used as medicines. The Makekal, Air Hitam, and Terap used 11 species, 9 species, and 4 species, respectively. Parts of animals used as medicines included the whole body, meat, bile, heart, and scale. They were used to treat various diseases such as fever, itchy, antidote, stamina, stomach ache, measles, heat sink, kidney diseases, asthma, and shortness of breath. The animals that were used as medicines included snake sapodilla (Malayopython reticulatus), porcupine (Hystris sumatrae), long-tailed monkey (Macaca fascicularis), javan pangolin (Manis javanica), three-striped squirrel (Callosciurus prevostii), cave bat (Chiroptera sp.), turtle/labi-labi (Dogania subplana), and tapah fish (Wallago attu). The local wisdom of Orang Rimba is indicated to changes such as the use of health facilities and modern medicines instead of animals as medicines and the shift of traditional orientation in animal use to the economy orientation.